2017
DOI: 10.1017/s2045796017000361
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations in generalised anxiety disorder: a review of proton magnetic resonance spectroscopic studies

Abstract: This Section of Epidemiology and Psychiatric Sciences appears in each issue of the Journal to stress the relevance of epidemiology for behavioral neurosciences, reporting the results of studies that explore the use of an epidemiological approach to provide a better understanding of the neural basis of major psychiatric disorders and, in turn, the utilisation of the behavioural neurosciences for promoting innovative epidemiological research.The ultimate aim is to help the translation of most relevant research f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Etkin et al15 have also found evidence of an intra-amygdala abnormality with engagement of a compensatory fronto-parietal executive control network, consistent with cognitive theories of GAD. Interestingly, a recent review reported selective metabolic dysfunctions in regions within the prefrontal-limbic network, including the dorsolateral prefrontal cortex (DLPFC) and hippocampus 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etkin et al15 have also found evidence of an intra-amygdala abnormality with engagement of a compensatory fronto-parietal executive control network, consistent with cognitive theories of GAD. Interestingly, a recent review reported selective metabolic dysfunctions in regions within the prefrontal-limbic network, including the dorsolateral prefrontal cortex (DLPFC) and hippocampus 16…”
Section: Introductionmentioning
confidence: 99%
“…With regard to neurochemistry, a number of neurotransmitter systems have been implicated in the neurobiology of GAD 16,26,27. Given the known pharmacological and clinical effects of benzodiazepines, the γ-aminobutyric acid (GABA)/benzodiazepine system has become a focus of research in GAD.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with anxiety, changes in brain function and structure as well as metabolic abnormalities are known to occur [ 24 , 25 ].In this connection, Harper et al found a correlation between choline concentration and negative mood in patients with chronic pelvic pain syndrome [ 26 ]. Unique advantages of 1 HMRS are the ability to provide important quantitative biochemical information in localized brain areas, and to document brain metabolic activity efficiently in people with mood disorders [ 19 , 25 ]. In addition, an association has been reported between chronic headaches and central nervous system alterations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crude resolution of centimetres in MRS compared to millimetres in conventional MRI as well as the added scanning time needed to reliably generate robust spectra (increasing the possibility of subject movement) also limits the precision of this technique in brain research. However, despite these limitations, 1 H-MRS is becoming increasingly clinically relevant [47] and is also contributing to our understanding of diseases such as Parkinson’s disease [48], multiple sclerosis [49], epilepsy [50], depression [51], schizophrenia [52, 53], bipolar disorder [54, 55], and anxiety [56, 57].…”
Section: Introductionmentioning
confidence: 99%